YKL-40 promotes chemokine expression following drug-induced liver injury via TF-PAR1 pathway in mice - Jing-Lun, Zhan; Shuang, Chai; Li-Mei, Zhao; Xiao-Dong, Liu (Frontiers in Pharmacology, 2023)
Background: The inflammatory factor YKL-40 is associated with various inflammatory diseases and is key to remodeling inflammatory cells and tissues. YKL-40 (Chi3l1) promotes the activation of tissue factor (TF), leading to intrahepatic vascular coagulation (IAOC) and liver injury. TF is a key promoter of the exogenous coagulation cascade and is also involved in several signaling involving cell proliferation, apoptosis, charring, migration and inflammatory diseases pathways. However, the effect of YKL-40-induced TF-PAR1 pathway on the expression of downstream chemokines remains unknown. Methods: We established a liver injury model using Concanavalin A (ConA) in C57 BL/6 mice. By adopting various experimental techniques, the effect of YKL-40 induced TF-PAR1 pathway on the expression of downstream chemokine ligand 2 (CCL2) and IP-10 was verified. Results: We found that overexpression of YKL-40 increased the expression of TF, protease-activated receptor 1 (PAR1), CCL2 and IP-10 in mice and exacerbated the severity of liver injury. However, blocking the expression of TF significantly reversed the extent of liver injury. Conclusion: We found that YKL-40 promotes the expression of downstream chemokines ligand 2 (CCL2) and IP-10 by activating the TF-PAR1 pathway, leading to increased recruitment of inflammatory cells and exacerbating the progression of liver injury. This provides a new approach for the clinical treatment of drug-induced liver injury.